When a close person suddenly changes their behavior – dementia in young people. A case report - Wiśniewska-Skomra, Joanna; Tylutka, Kinga; Hapon, Anna; Zapała, Magdalena; Hunek, Adrian; Kaziród, Karolina; Chmielarz, Karolina; Dadziak, Mikołaj (Journal of Education, Health and Sport, 2023)
The aim of our study is to present a case report of a young patient with rapidly progressive behavioral changes. A 39-year-old well functioning man in a short period of time began to show symptoms like agressive towards his family members, binge eating, apathy, difficulties with social interactions, reduced verbal fluency and poverty of speech, disorders in executive functions and restlessness and anxiety. This behavioral changes appeared in a short period of time (6 months). The concerned family, alarmed by this unusual behavior not previously observed, sought medical help. The patient was disoriented, not receptive to arguments about his atypical behavior, and unaware of the existing problem. A comprehensive diagnostic evaluation (including laboratory, imaging, and neuropsychological assessments) was conducted during the hospital stay. MRI scan showed substantial cortical atrophy in frontal and temporal lobes. Based on the clinical status, typical MRI and neuropsychological examination, the patient was diagnosed with frontotemporal dementia (FTD). The patient received a diagnosis in a very short period of time, which is not typical in establishing a diagnosis for this particular medical condition. The symptoms are often nonspecific, which delays the diagnosis or leads to an incorrect preliminary diagnosis of another medical condition. Difficulties in diagnosing also arise from the non-specific symptoms, which are often overlooked by the patient themselves. It is important to emphasize the crucial role of family members and close associates in recognizing the initial symptoms and making attempts to diagnose the disease. It is also important to provide support and care for the patient's family, for whom the diagnosis of FTD becomes challenging and burdening.